2023
DOI: 10.1088/2515-7655/acb96d
|View full text |Cite
|
Sign up to set email alerts
|

Polarons in perovskite solar cells: effects on photovoltaic performance and stability

Abstract: Organic-inorganic hybrid perovskites manifest unique photophysical properties in terms of long carrier lifetime, low recombination rate and high defect tolerance, enabling them promising candidates in optoelectronic devices. However, such advancing properties are unexpected in the perovskite materials with moderate charge mobility. Recent investigations have revealed that these appealing properties were endowed as the formation of large polarons in perovskite crystals due to the coupling of photogenerated carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 99 publications
(168 reference statements)
0
5
0
Order By: Relevance
“…Based predominantly on evidence from DFT studies , and optical experiments, Cs 2 TiBr 6 has been identified as a promising thin-film solar cell absorber material. , However, highly efficient hybrid organic–inorganic solar cell absorbers show exciton binding energies ∼15 meV, , enabling rapid thermal dissociation of the exciton (at k B T ∼ 25 meV), and the subsequent formation of Wannier–Mott polarons. It has been proposed that weakly bound polarons reduce recombination rates while retaining moderate charge carrier mobility. The large difference between the fundamental and optical bandgaps of Cs 2 TiBr 6 at zero-temperature indicates significant exciton binding and electron–phonon interaction energies, apparently precluding Cs 2 TiBr 6 as an efficient solar cell absorber. Alternatively, this work supports applications for Cs 2 TiBr 6 such as white LEDs, broadband photodetectors, or lasers. ,, Accurate spectral properties are important in the design of new ionic semiconductors for diverse applications ranging from solar cells to memristors and pressure induced emission .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based predominantly on evidence from DFT studies , and optical experiments, Cs 2 TiBr 6 has been identified as a promising thin-film solar cell absorber material. , However, highly efficient hybrid organic–inorganic solar cell absorbers show exciton binding energies ∼15 meV, , enabling rapid thermal dissociation of the exciton (at k B T ∼ 25 meV), and the subsequent formation of Wannier–Mott polarons. It has been proposed that weakly bound polarons reduce recombination rates while retaining moderate charge carrier mobility. The large difference between the fundamental and optical bandgaps of Cs 2 TiBr 6 at zero-temperature indicates significant exciton binding and electron–phonon interaction energies, apparently precluding Cs 2 TiBr 6 as an efficient solar cell absorber. Alternatively, this work supports applications for Cs 2 TiBr 6 such as white LEDs, broadband photodetectors, or lasers. ,, Accurate spectral properties are important in the design of new ionic semiconductors for diverse applications ranging from solar cells to memristors and pressure induced emission .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to conventional semiconductors, MHPs are polar materials where excited charge carriers can distort the ionic lattice creating a potential well, where they are self-trapped as a polaron . There has been increasing evidence that polaronic trapping in a soft, ionic crystalline lattice facilitates the spatial separation of excited charge carriers, resulting in decreased recombination rates combined with moderate carrier mobilities. In addition, excitons with short lifetimes can facilitate the efficient absorption of solar radiation. Hybrid organic–inorganic MHP thin-film solar cell absorbers have achieved certified power conversion efficiencies (PCE) of up to 26.1% for a single-junction at low-cost, with the possibility of layered absorbers to further increase PCE. ,, However, stability and lead-toxicity impede their large-scale commercialization. …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Benefiting from the hybrid composition, halide perovskites exhibit excellent properties such as adjustable band gap, high carrier mobility, large optical absorption coefficient, small exciton binding energy, and solution processability. [12][13][14][15][16][17] These properties are crucial to achieve high performance and low cost solar cells.…”
Section: Shengqiao Zengmentioning
confidence: 99%
“…Polarons have a profound impact on material properties such as electron−phonon interactions, charge transport, and ion migration and, therefore, affect device functionalities and efficiencies. 6 Halide perovskites are a promising class of optoelectronic material. Both small polarons and large polarons are present in halide perovskites due to their ionic lattice with large polarity, playing an important role in properties such as charge transport and phase segregation.…”
Section: Introductionmentioning
confidence: 99%
“…Small polarons are trapped on a single ion, while large polarons move in a band with a large effective mass. Polarons have a profound impact on material properties such as electron–phonon interactions, charge transport, and ion migration and, therefore, affect device functionalities and efficiencies …”
Section: Introductionmentioning
confidence: 99%